H2O2 induces PP2A demethylation to downregulate mTORC1 signaling in HEK293 cells. (13th June 2018) - Tang, Shen; Qin, Fu; Wang, Xinhang; Liang, Ziwei; Cai, Haiqing; Mo, Laiming; Huang, Yue; Liang, Boyin; Wei, Xuejing; Ao, Qingqing; Xu, Yilu; Liu, Yuyang; et al.
Abstract: Mammalian target of rapamycin (mTOR) is a Ser/Thr protein kinase that functions as an ATP and amino acid sensor to govern cell growth and proliferation by mediating mitogen‐ and nutrient‐dependent signal transduction. Protein phosphatase 2A (PP2A), a ubiquitously expressed serine/threonine phosphatase, negatively regulates mTOR signaling. Methylation of PP2A is catalyzed by leucine carboxyl methyltransferase‐1 (LCMT1) and reversed by protein phosphatase methylesterase 1 (PME‐1), which regulates PP2A activity and substrate specificity. However, whether PP2A methylation is related to mTOR signaling is still unknown. In this study, we examined the effect of PP2A methylation on mTOR signaling in HEK293 cells under oxidative stress. Our results show that oxidative stress induces PP2A demethylation and inhibits the mTORC1 signaling pathway. Next, we examined two strategies to block PP2A demethylation under oxidative stress. One strategy was to prevent PP2A demethylation using a PME‐1 inhibitor; the other strategy was to activate PP2A methylation via overexpression of LCMT1. The results show that both the PME‐1 inhibitor and LCMT1 overexpression prevent the mTORC1 signaling suppression induced by oxidative stress. Additionally, LCMT1 overexpression rescued cell viability and the mitochondrial membrane potential decrease in response to oxidative stress. These results demonstrate that H2 O2 induces PP2A demethylation to downregulate mTORC1 signaling. These findings provide a novel mechanism for the regulation of PP2A demethylation and mTORC1 signaling under oxidative stress.